De la literatura latinoamericana a la literatura (latinoamericana) mundial Condiciones materiales, procesos y actores - Locane, Jorge J. (Latin American Literatures in the World / Literaturas Latinoamericanas en el Mundo, 2019)
What is World Literature? To answer this question, this book asks another one: How is it produced, that is, what are the material conditions, processes, and actors, which enable Latin-American Literature to circulate internationally and become (Latin-American) World Literature? Exploring the tension between literature for and of the world, the volume also intend to give visibility-and value as World Literature- to local forms of expression.